2017
DOI: 10.1177/2309499017690461
|View full text |Cite
|
Sign up to set email alerts
|

Can local infiltration analgesia increase satisfaction in postoperative short-term pain control in total knee arthroplasty?

Abstract: Background: One of the major challenges to total knee arthroplasty (TKA) is optimal pain control. Effective analgesia is capital in fast-track surgery programs to allow patient's early functional outcomes. Objectives: Compare length of stay (LOS) short-term pain control, and patients' satisfaction at 1 month between local infiltration analgesia (LIA) combined with femoral nerve block (FNB) and FNB only in patients undergoing TKA. Patients and methods: Two hundred and fifty-four patients were included in a rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 40 publications
(79 reference statements)
1
16
0
Order By: Relevance
“…According to the current literature data, all these anesthetics do show a good local analgesic effect. [1][2][3][4][5][6][7] Over and above that, a cell-toxic effect could be also observed in several studies dedicated to cartilage ( Table 1). 13,[15][16][17] At present, there is to our knowledge however no uniform recommendation as to which anesthetic should definitely be used for local joint infiltration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the current literature data, all these anesthetics do show a good local analgesic effect. [1][2][3][4][5][6][7] Over and above that, a cell-toxic effect could be also observed in several studies dedicated to cartilage ( Table 1). 13,[15][16][17] At present, there is to our knowledge however no uniform recommendation as to which anesthetic should definitely be used for local joint infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…Here they are used in the form of a local infiltration anesthesia (LIA) and show comparably good analgesic effects, for example, during the utilization of pain catheters. 3,[5][6][7] Lidocaine, ropivacaine, and bupivacaine contribute to the most often-used LAs. Nevertheless, until this day there is no uniform recommendation as to which local anesthetic for joint injection is best suited.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 There is increasing evidence to support the use of LIA in TKA. [4][5][6][7][8] However, other studies have shown that the efficacy of LIA during TKA is not superior to that of previously available methods. [9][10][11] In addition, the use of LIA is reportedly safe, 1,[12][13][14][15] but has only recently been adopted in medical centres in Hong Kong.…”
Section: 局部麻醉於全膝關節置換術中應用的效果mentioning
confidence: 99%
“…Effective analgesia is a key component of fast-track surgery programs to allow patients early functional outcomes [21,22].…”
Section: Analgesic Protocol In Patients Undergoing Tkrmentioning
confidence: 99%